Locating emergency vehicles: Modelling the substitutability of resources and the impact of delays in the arrival of assistance - Nelas, José (2021)
The quality and promptness of emergency assistance is highly dependant on the location of existing emergency vehicles. In this work, we propose a new model for optimizing emergency vehicles’ location that takes into account the existence of different types of emergency vehicles and the level of care they can provide, the possibility of vehicles’ substitution considering the hierarchy of levels of care and the explicit consideration of the progression of an emergency episode when the arrival of assistance suffers delays. The inherent uncertainty that exists in this problem is represented by a set of scenarios. A heuristic procedure for solving the problem was also developed. The model and algorithmic approach were tested using real data. It is possible to conclude that the application of stochastic location models that explicitly consider the evolution of the health condition of the victims when care is delayed can lead to better emergency coverage. The location of vehicles is indeed influenced by the explicit consideration of the impact of assistance time on the victims’ conditions.